The Use of Probiotics to Prevent Diarrhoea in Young Children Attending Child Care Centers: A Review - Binns, Colin; Lee, M. (Elsevier BV, 2010)
The incidence of diarrheal disease in children has been reduced because of public health measures,improved hygiene, and a better understanding of nutrition. However, it remains a particular problemwhere young children come into close contact with other children, such as in child day care centers.Probiotics are defined as products that contain an adequate dose of live microbial agents that have beenshown in target-host studies to confer a health benefit. They have been used for the treatment andprevention of many diseases, but particularly of gastrointestinal diseases. Prebiotics are inactive foodcomponents, commonly oligosaccharides or polysaccharides, that stimulate growth of beneficial bacteriain the gastrointestinal tract and are commonly used in combination with probiotics.The initial searches identified 5860 articles from the PubMed database, but only 154 included thekeyword ?trial.? Probiotics share the problem of limited systematic research with other traditionalmedications and foods, and only seven studies were included in the final analysis. A variety of probioticorganisms and prebiotics were used in the studies, and the end points were not standardized. However,examination of the six studies that used live cultures showed that five studies resulted in a decrease ineither the number of episodes or the duration of diarrhea or both. However, the studies supporta reduction of around 20% in diarrheal episodes or days of illness. Findings of this review have importantimplications for working parents. The regular use of a probiotic or probiotic/prebiotic combination willreduce the incidence and duration of diarrheal disease in children attending childcare centers (risk ratio,0.72e0.82). Further research is needed to better define the most effective probiotic organisms and theoptimal dosage